Sustaining soil productivity in response to global climate change : science, policy, and ethics - Sauer, Thomas J.; Norman, John M.; Siva Kumar, M. V. K.; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
"Sustaning Soil Productivity in Response to Global Climate Change is a two-part text bringing together the latest research in soil science and climatology and the ethical, political and social issues surrounding the stewardship of this vital resource. Chapters include scientific studies on microbial function, maintaining fertility, and the effects of greenhouse gas emissions, as well as ethical issues ranging from allocation of land use to policies needed for conservation. Based on topics presented by speakers at the Organization for Economic Cooperation and Development's conference, this text is internationally contributed to by experts in the field"--
Front Matter -- Science, Ethics, and the Historical Roots of Our Ecological Crisis / Thomas J Sauer, Michael P Nelson -- Intellectual Inertia / John M Norman -- The Ethics of Soil / Paul B Thompson -- Aldo Leopold and the Land Ethic / Susan L Flader -- Rural Response to Climate Change in Poor Countries / C J (Kees) Stigter -- Soil and Human Health / Eiliv Steinnes -- Agroecological Approaches to Help Climate Proof Agriculture While Raising Productivity in the Twenty-First Century / Norman Uphoff -- Ecological Integrity and Biological Integrity / Laura Westra -- Soil Ecosystem Services / Brent E Clothier, Alistair J Hall, Markus Deurer, Steven R Green, Alec D Mackay -- Climate and Land Degradation / Mannava V K Sivakumar -- The Role of Soils and Biogeochemistry in the Climate and Earth System / Elisabeth A Holland -- Net Agricultural Greenhouse Gases / Claudia Wagner-Riddle, Alfons Weersink -- Overview on Response of Global Soil Carbon Pools to Climate and Land-Use Changes / Thomas Eglin, Philippe Ciais, Shi Long Piao, Pierre Barř, Valentin Belassen, Patricia Cadule, Claire Chenu, Thomas Gasser, Markus Reichstein, Pete Smith -- Potential Impacts of Climate Change on Microbial Function in Soil / Paolo Nannipieri -- Impacts of Climate Change on Forest Soil Carbon / Philip J Polglase, Keryn I Paul -- The Effect of Forest Management on Soil Organic Carbon / Giustino Tonon, Silvia Dezi, Maurizio Ventura, Francesca Scandellari -- Index -- Keep up with Critical Fields.
Includes bibliographical references and index.
Print version record.
Keywords: Soil management; Sustainable agriculture; Greenhouse gas mitigation; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Soil Science; Agriculture; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Soil Science; Greenhouse gas mitigation; Soil management; Sustainable agriculture; Electronic books